Percepção ambiental, conhecimento e uso de recursos vegetais no assentamento agroextrativista São Sebastião, Pirambu, Sergipe - Oliveira, Débora Moreira de (2012)
The restinga ecosystem has been one of the most impacted in Brazil due to its coastal location, where the housing boom and Unregulated tourism are the main factors degrading. The northern coast of Sergipe is included in this reality, mainly due to the unique beauty of the region. Attempts to conserve species has been scarce and recent, still requiring more structure to the units of local conservation. In order to meet both the conservation of natural resources on improving socioeconomic conditions in the region was created in the municipality of Pirambu, a rural settlement land reform mode agroextractive: Assentamento Agroextrativista São Sebastião. The settlement covers 28 families, who were residents of nearby land currently regulated, and which have as their main economic activities in the extraction of mangaba (Harconia speciosa L.), handicrafts from the straw ouricurizeiro (Siagrus coronata Beccari Matius) and family farming. The objective of this study was to investigate how does the relationship between man and the environment botanist, with the methods and techniques employed by the ethnobotany, in order to raise possible discussions about the sustainability of these resources in the settlement. For better understanding and organization of data, this study is divided into four chapters. Chapter 1 presents a brief review of the main authors and themes related to the research , as well as a characterization of the study area, based on available literature and data obtained in the field. Chapter 2 it is a collection of botanical species considered useful by the residents. In this, we performed a general characterization of the study area, based on socioeconomic information provided by residents, associated with the listing of all known species useful. The 106 species listed were grouped into seven categories of use, and some were inserted in more than one category, namely: Food (43), Medical (46), Fuel (22), Craft (3), Mystic-religious (10), Ornamental (6) and Other (5). The species were classified according to their use and value to the category Fuel, we applied the technique of Rapid Spatial Insider. Chapter 3 was a specific study of the homegardens of the town. Twenty-five homegardens have been visited and all species with diameter at ground level were recorded ≥ 3, and computed their heights, canopy and location in space in the homegarden. Was investigated the importance of the yard to keep the family through semi-structured, and the division of labor and management techniques employed. Chapter 4 was a study with the objective of understanding the relation between the children of school-age settlement compatible to the elementary school and the local environment. We used a triangulation of methods to achieve the desired responses: making individual drawings, map-making and collective application of semi-structured interviews. Data from several studies point to a wealth of local biodiversity yet little explored, as opposed to certain species that may be under pressure to use, thus concluding the need for further multidisciplinary studies that value local knowledge in building strategies for sustainable development in the settlement that the name itself shows the proposal to use natural resources rationally, socioeconomic and environmental justice.